Peptides Derived from Vascular Endothelial Growth Factor B Show Potent Binding to Neuropilin‐1. (3rd November 2021) - Mota, Filipa; Yelland, Tamas; Hutton, Jennie A.; Parker, Jennifer; Patsiarika, Anastasia; Chan, A. W. Edith; O'Leary, Andrew; Fotinou, Constantina; Martin, John F.; Zachary, Ian C.; Djordjevic, Snezana; Frankel, Paul; et al.
Abstract: Vascular endothelial growth factors (VEGFs) regulate significant pathways in angiogenesis, myocardial and neuronal protection, metabolism, and cancer progression. The VEGF‐B growth factor is involved in cell survival, anti‐apoptotic and antioxidant mechanisms, through binding to VEGF receptor 1 and neuropilin‐1 (NRP1). We employed surface plasmon resonance technology and X‐ray crystallography to analyse the molecular basis of the interaction between VEGF‐B and the b1 domain of NRP1, and developed VEGF‐B C‐terminus derived peptides to be used as chemical tools for studying VEGF‐B ‐ NRP1 related pathways. Peptide lipidation was used as a means to stabilise the peptides. VEGF‐B‐derived peptides containing a C‐terminal arginine show potent binding to NRP1‐b1. Peptide lipidation increased binding residence time and improved plasma stability. A crystal structure of a peptide with NRP1 demonstrated that VEGF‐B peptides bind at the canonical C‐terminal arginine binding site. VEGF‐B C‐terminus imparts higher affinity for NRP1 than the corresponding VEGF‐A165 region. This tight binding may impact on the activity and selectivity of the full‐length protein. The VEGF‐B167 derived peptides were more effective than VEGF‐A165 peptides in blocking functional phosphorylation events. Blockers of VEGF‐B function have potential applications in diabetes and non‐alcoholic fatty liver disease. Abstract : VEGF‐B binds to the b1 domain of neuropilin‐1. VEGF‐B‐derived peptides show potent binding to neuropilin‐1 (KD =0.13 to 9.55 μM) and inhibit binding of VEGF‐A in a cell‐based assay (IC50 =0.3 to 2.0 μM). Peptide lipidation increased binding and plasma half‐lives.